"Eu vinha rodando pela rua": que ponto de ancoragem para o sujeito adolescente em situação de rua? - Barros, Paula Cristina Monteiro de (2015)
The presence of "street kids" denounces the social exclusion of children and adolescents that wander the streets, in a trajectory that prevails transgression, violence, destructivity, through which the subject persists to exist for the Other. This thesis is a result of questionings from a clinical practice in an institution. This thesis envisions to analyze what could be related to an anchorage and enlacing in the wander of homeless adolescents, based on the traces that make them unique and detached from the universe of street kids . We propose the hypothesis that the wander, regardless of the subjective degradation and the expulsion, could constitute a movement of life and resistance, an emergence of the subject. Based on the psychoanalytic Trace of the Case, this research was guided by two clinical cases, from what constituted an intervention s stumble and its effects in the listening process. Guided by the Freudian Aufhebung and the Lacanian borromean knot, we highlight a reality characterized by the fraying of time and space, a dilution of boundaries, a prevalence of the Real. The proposition of a borromean clinic places the institution as a symbolic reference; a substitute that functions, utilizing the word as a resource, as a repair to the lapses of the knot. This is about a construction that transgresses what is institutionalized about exclusion, knowledge, and established clinical practice. It aims, through an inventive act, a trajectory from the wound of the exclusion to the draft of a trace, through a symbolic nomination; a between space that promotes the knot and the social engagement; a source of anchorage for whom used to go rolling through the street .